EXPRESSION OF b-XYLOSIDASE ENCODING GENE IN PHIS/ Bacillus megaterium MS SYSTEM - Sumarsih, Sri (Indonesian Journal of Tropical and Infectious Disease, 2011)
b-Xylosidase encoding gene from G. thermoleovorans IT-08 had been expressed in the pHIS1525/ B. megaterium MS941 system. The b-xylosidase gene (xyl) was inserted into plasmid pHIS1525 and propagated in E. coli DH10b. The recombinant plasmid was transformed into B. megaterium MS941 by protoplast transformation. Transformants were selected by growing the recombinant cells on solid LB medium containing tetracycline (10 µg/ ml). The expression of the b-xylosidase gene was assayed by overlaid the recombinant B. megaterium MS941 cell with agar medium containing 0.2% ethylumbelliferyl-b-D-xyloside (MUX). This research showed that the b-xylosidase gene was succesfully sub-cloned in pHIS1525 system and expressed by the recombinant B. megaterium MS941. Theaddition of 0.5% xylose into the culture medium could increase the activity of recombinantactivity of recombinant of recombinantb-xylosidase by 2.74 fold. The recombinant B. megaterium MS941 secreted 75.56% of the expressed b-xylosidase into culture medium. The crude extract b-xylosidase showed the optimum activity at 50° C and pH 6. The recombinant b-xylosidase was purified from culture supernatant by affinity chromatographic method using agarose containing Ni-NTA (Nickel-Nitrilotriacetic acid). The pure b-xylosidase showed a specific activity of 10.06 Unit/mg protein and relative molecular weight ± 58 kDa.